Facile fabrication of silk fibroin/graphene oxide composite films and real‐time morphological observation in stretching. Issue 47 (22nd July 2021) - Shang, Zihan; Yan, Yinan; Jiang, Jie; Wang, Jielin; Yin, Xiaoying
Abstract: Layer‐structured regenerated silk fibroin (SF)/graphene oxide (GO) composite films were fabricated by a facile solution casting method. Fourier transform infrared spectroscopy, X‐ray diffraction, and thermal gravity analysis confirmed the successful incorporation and uniform dispersion of graphene oxides in the SF matrix. To visualize GO's effect on the morphological evolution, atomic force microscopic images were recorded in real‐time during the composite elongation to establish a correlation between microscopic structural characters and macroscopic mechanical properties. The result showed that the incorporation of graphene oxide into the SF matrix resulted in chain conformational transition, film surface flattening, and mechanical reinforcement. Surface roughness dramatically decreased from 65 to 10 nm, while tensile modulus increased substantially from 8.61 to 22.37 MPa by adding well‐dispersed graphene oxide up to 1 wt% into the SF matrix. Through the real‐time AFM observation under the horizontal stretching mode, the surface topography of original SF films varied from tori‐spherical aggregations to rod‐like ones resulting from GO's incorporation. In the meantime, SF's hydrophobicity was also increased, as manifested by contact angle increase from 30.81° to 45.09°. Abstract : Layer‐structured silk fibroin (SF)/graphene oxide (GO) composite films were fabricated by facile solution casting method, and related atomic force microscopic images were recorded in real‐time during the film elongation. The surface topography of original SF films varied from tori‐spherical aggregations to rod‐like ones resulting from the incorporation of planar GO fillers and horizontal tensile strength.